1996
DOI: 10.1002/(sici)1097-4547(19961015)46:2<204::aid-jnr8>3.3.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Schwann cells stimulated by axolemma‐enriched fractions express cyclic AMP responsive element binding protein

Abstract: Both axolemma-enriched fractions (AEF) and cyclic AMP have been shown to regulate the proliferation and differentiation of cultured primary Schwann cells (SC). We have evaluated the role of CREB, a transcription factor that binds to the cAMP-responsive element, in mediating the AEF-stimulated SC proliferation and differentiation. We detected CREB in nuclear extracts derived from SC stimulated with 40 micrograms/ml of AEF for 16, 24, 48, 72, and 96 hr, using a DNA-electrophoretic mobility shift assay. Unstimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Modification of cAMP levels in Schwann cells is associated with changes in morphological and functional parameters, including proliferation, differentiation and synthesis of myelin proteins (LeBlanc et al ., 1992; Lee et al ., 1996, 1999; Mirsky & Jessen, 1999; Mirsky et al ., 2001). Given our demonstration that Schwann cell GABA B receptors are negatively coupled to adenylate cyclase, we evaluated whether baclofen might modify the proliferation of Schwann cells induced by forskolin.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Modification of cAMP levels in Schwann cells is associated with changes in morphological and functional parameters, including proliferation, differentiation and synthesis of myelin proteins (LeBlanc et al ., 1992; Lee et al ., 1996, 1999; Mirsky & Jessen, 1999; Mirsky et al ., 2001). Given our demonstration that Schwann cell GABA B receptors are negatively coupled to adenylate cyclase, we evaluated whether baclofen might modify the proliferation of Schwann cells induced by forskolin.…”
Section: Resultsmentioning
confidence: 99%
“…Schwann cells have the potential to proliferate during normal PNS development and after neuronal injury (Lee et al ., 1996, 1999; Mirsky & Jessen, 1999). During these processes, axonal signals, which may function as activators of adenylate cyclase, exert an important role in the proliferation of peripheral glia (Lee et al ., 1996, 1999; Mirsky & Jessen, 1999). Consequently, having demonstrated that in common with the situation in the CNS (Knight & Bowery, 1996) and in the PNS, GABA B receptor agonists modulate cAMP levels, we further evaluated whether activation of such receptors in Schwann cells might affect cellular proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this possibility appears to be unlikely since Raible and McMorris (1993) have shown that treatment of cultures with db-CAMP induced a wave of oligodendrocyte differentiation but inhibited proliferation of the progenitor cells. In this regard, it is interesting to note that in Schwann cells CREB expression is closely correlated to proliferation (Lee et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Although ␤ neuregulin does not induce immediate elevation of intracellular cAMP levels in cultured Schwann cells there is a transient elevation of cAMP levels in Schwann cells about 12 hours after addition of ␤ neuregulin (86). One of the signaling pathways used appears to involve the transcription factor CREB (95,158). ␤ neuregulin induces CREB phosphorylation within 5 minutes of application, probably acting via the MAP kinase pathway.…”
Section: Neuregulins and Schwann Cellsmentioning
confidence: 97%